The Limitations of a Guest Doctor's Liability Due to Negligence in Social Service Activities - Wulan, Afni Oktaria Sarining; Putera, Andika Persada (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Hospitals try to always meet the community’s need for health services, one of which is through social service activities, including free medical treatment, mass circumcision, free cataract surgery, cleft lip surgery, and so on. In these social service activities, doctors are usually given an assignment letter from the hospital institution in the form of an assignment letter or an invitation to take part in these activities, in practice they are often called guest doctors. This study aims to analyze the legal relationship between guest doctors and hospital agencies in the implementation of social service activities, and to analyze the limits of guest doctors’ liability in social service activities in hospitals that cause patient losses. This study uses normative legal research methods. The legal relationship between guest doctors and hospitals that carry out social service activities, namely special agreement legal relationships based on work agreements with hospitals, where guest doctors are the parties who perform treatment or provide health services to patients, while hospitals are the parties that provide places and facilities for health services. That this visiting doctor is legally domiciled under the auspices of the hospital. The limits of guest doctor's liability in social service activities at the hospital that cause harm to patients, namely guest doctors with the hospital are proportionally responsible according to the provisions at the hospital based on the agreed work agreement.